Ludo Edutainment: A Media to Improving Knowledge and Attitude about HIV-AIDS Among Senior High School Students in Yogyakarta - Meilani, Niken; Setiyawati, Nanik; Rofi'ah, Siti; Sukini, Tuti; Wibowo, Queenaisya Elfaiza (Universitas Airlangga, 2025)
Background: Indonesia had the third-highest number of new HIV/AIDS cases in the Asia-Pacific. Adolescents are more vulnerable, for almost half of all new cases worldwide. HIV/AIDS cases among 15–19-year-olds have increased in Indonesia for the last three years. Media is necessary to increase teenagers' awareness of and favorable attitudes about HIV/AIDS prevention. Objective: This study assessed the influence of the Ludo Healthy Smart Game on adolescents’ knowledge and positive attitudes toward HIV/AIDS prevention. Methods: The study was quasi-experimental with a non-equivalent control group design. Senior high school students in Yogyakarta were the study samples. There were 130 respondents divided into two groups. Questionnaires used for data collection have been subject to validity and reliability tests. Univariate and bivariate data analyses were used. Results: This study found that the Ludo Healthy Smart Game is effective in improving adolescents’ knowledge about HIV/AIDS (p=0.000). The Ludo Healthy Smart Game does not affect positive attitudes toward HIV/AIDS prevention (p<0.005). However, there was an improvement in adolescents’ attitudes following the treatment. Conclusion: The Ludo Healthy Smart Game can be used as health educational media to increase knowledge about HIV/AIDS among adolescents. The higher the adolescents’ knowledge about HIV/AIDS, the better their behavior toward HIV/AIDS prevention.